2017
DOI: 10.1002/eat.22715
|View full text |Cite
|
Sign up to set email alerts
|

Labeling and defining severe and enduring anorexia nervosa: A systematic review and critical analysis

Abstract: It is the aim of the authors to inspire further research into what is the most appropriate label and defining features for the subgroup in order to facilitate a better approach and outcome for the individuals affected.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
109
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(111 citation statements)
references
References 61 publications
(86 reference statements)
2
109
0
Order By: Relevance
“…Such precession of age at onset does not seem to be a random phenomenon, as it is related to specific clinical and psychological features and to a less favourable course (Abbate‐Daga et al, ). Clearly, in those cases, a longer time needed to reach specialist ED care may imply the risk of higher degrees of chronicity and a worse outcome (Broomfield, Stedal, Touyz, & Rhodes, ). Although experts in the field have recently pleaded for the introduction of an “early intervention” approach for EDs and the reduction in the time of untreated symptoms in EDs, they have also recognized that in order to achieve such goals, services will need to be reconfigured to match different clinical phases and settings in the future (Treasure & Russell, ).…”
Section: Discussionmentioning
confidence: 99%
“…Such precession of age at onset does not seem to be a random phenomenon, as it is related to specific clinical and psychological features and to a less favourable course (Abbate‐Daga et al, ). Clearly, in those cases, a longer time needed to reach specialist ED care may imply the risk of higher degrees of chronicity and a worse outcome (Broomfield, Stedal, Touyz, & Rhodes, ). Although experts in the field have recently pleaded for the introduction of an “early intervention” approach for EDs and the reduction in the time of untreated symptoms in EDs, they have also recognized that in order to achieve such goals, services will need to be reconfigured to match different clinical phases and settings in the future (Treasure & Russell, ).…”
Section: Discussionmentioning
confidence: 99%
“…This finding should be interpreted cautiously because this study may have been under-powered to detect the association between duration of AN and RSFC patterns and the measure used to establish duration of illness was somewhat imprecise. Additionally, although illness duration suggested that participants were, on average, beyond the early stages of AN (Broomfield et al, 2017), it is possible that the illness duration range was too narrow to capture effects of illness chronicity on frontostriatal circuitry. However, this finding could also suggest that patterns of heterogeneity in brain functioning among individuals with AN differ according to variables other than length of illness.…”
Section: Discussionmentioning
confidence: 99%
“…However, this model further asserts that the over-training of such reward responses to illness-compatible stimuli eventually fosters a compulsive reliance on rigid and automatic eating disorder behaviors, independent of momentary dopaminergic responding (Foerde, Steinglass, Shohamy, & Walsh, 2015; Godier & Park, 2014). Thus, the habit-centered model deviates from the reward deficit model in postulating that, once an individual has fully developed AN, especially after the initial stages of illness (e.g., adolescence, <3–5 years of illness; Broomfield, Stedal, Touyz, & Rhodes, 2017), dysfunctions in dorsal frontostriatal network predominate over those in more ventral, reward-oriented regions (Godier & Park, 2014; Walsh, 2013). …”
Section: Introductionmentioning
confidence: 99%
“…Lifetime prevalence of AN is estimated to be 3.64% amongst women (Micali, Martini, et al, ), with AN incidence highest during adolescence (Micali, Hagberg, Petersen, & Treasure, ). Generally time to recovery is protracted (Strober, Freeman, & Morrell, ; Zerwas et al, ), and a significant proportion of individuals experience severe and enduring AN (Broomfield, Stedal, Touyz, & Rhodes, ), meeting full diagnostic criteria for many years (Steinhausen, ).…”
Section: Introductionmentioning
confidence: 99%